Kebijakan Gerbong Khusus Perempuan dan Ketimpangan Gender dalam Transportasi Publik: Studi Pengguna KRL di Jakarta - Farsya Ellysya; Nur Azizah Hikmatulloh; Zafirah Irdina Mulyana; Aniqotul Ummah; Teddy Chrisprimanata Putra (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This study examines the policy of women-only train cars and gender inequality in public transportation, particularly the KRL commuter line in Jakarta. The research is motivated by the continuing issues of safety and comfort experienced by women in their daily mobility within urban public spaces. The study aims to understand women’s experiences as KRL users, identify forms of gender inequality in public transportation, and analyze the implementation of women-only train car policies in everyday practice. This research employs a qualitative approach using semi-structured interviews with KRL users, field observations, and reviews of relevant documents and academic journals. The informants consist of female KRL users as the primary subjects and male users as comparative informants. The findings indicate that women still face issues related to safety concerns, overcrowding, and the risk of sexual harassment while using the KRL. The women-only train car policy is perceived as helping improve passengers’ sense of security; however, it has not fully resolved broader issues of gender inequality in public transportation. The study concludes that more inclusive transportation policies are needed through stronger security systems, better supervision, and the provision of safer public spaces for all users.